N-Substituted Pyrido-1,4-Oxazin-3-Ones Induce Apoptosis of Hepatocellular Carcinoma Cells by Targeting NF-κB Signaling Pathway - Mohan, Chakrabhavi Dhananjaya; Bharathkumar, Hanumantharayappa; Dukanya,; Rangappa, Shobith; Shanmugam, Muthu K.; Chinnathambi, Arunachalam; Alharbi, Sulaiman Ali; Alahmadi, Tahani Awad; Bhattacharjee, Atanu; Lobie, Peter E.; Deivasigamani, Amudha; Hui, Kam Man; et al. (Frontiers in Pharmacology, 2018)
Hepatocellular carcinoma (HCC) is a fatal disease and ranked fifth in cancer related mortality. Persistent activation of NF-κB is responsible for the oncogenesis, metastasis, tumor evasion, anti-apoptosis, angiogenesis and proliferation in HCC. Therefore, designing of chemically novel, biologically potent small molecules that target NF-κB signaling cascade have gained prominent clinical interest. Herein we synthesized a novel class of N-pyrido1,4-oxazine-4-ones by substituting hydrogen in N-H group of pyrido-1,4-oxazin-3-ones by using combustion derived bismuth oxide. We evaluated the antiproliferative efficacy of new oxazin-3-ones against HCC cells and identified 4-(4-nitrobenzyl)-2H-pyrido[3,2-b][1,4]oxazin-3(4H)-one (NPO) as lead anticancer agent. In addition, we investigated the effect of NPO on the DNA binding ability of NF-κB and NF-κB regulated luciferase expression in HCC cells. The results demonstrated that NPO can induce significant growth inhibitory effects in HepG2, HCCLM3 and Huh-7 cells in dose and time-dependent manner. Interestingly, NPO induced significant downregulation in p65 DNA binding ability, p65 phosphorylation and subsequent expression of NF-κB dependent luciferase gene expression in diverse HCC cell lines. Further, in silico docking analysis suggested that NPO can show direct physical interaction with NF-κB. Finally, NPO was found to significantly abrogate tumor growth at a dose of 50 mg/kg in an orthotopic mouse model. Thus, we report the potential anticancer effects of NPO as a novel inhibitor of NF-κB signaling pathway in HCC.